Narrative Functions in Burton’s Sleepy Hollow Movie - Devi Hellystia (Vivid: Journal of Language and Literature, 2021)
Narrative is the primary aspect of literary work. The quality of work is represented by narrative. In prose and drama, they both involve story and characters to present events in narrative. The writer chose to analyze narrative functions because the writer wanted to examine the validity of Propp’s theory which considers character’s action as fundamental element of narrative structure. In this research, the writer aimed to find out the narrative functions by analyzing character’s action and to know how the functions are depicted in the movie of Tim Burton’s Sleepy Hollow. The reason of this movie is analyzed since Sleepy Hollow movie had never been analyzed by other researchers. In analysis, the writer used Vladimir Propp’s model since it emphasizes character’s action as fundamental element of narrative structure. This research used formal method which excludes discussions concern with the creator as the main subject of research. the result showed that Sleepy Hollow movie is constructed by 25 functions such as interdiction, violation, reconnaissance, delivery, complicity, villainy, lack, mediation, beginning counteraction, departure, the first function of the donor, the hero’s reaction, provision or receipt of a magical agent, guidance, struggle, initial misfortune or lack is liquidated, return, pursuit, rescue, unrecognized arrival, difficult task, exposure, transfiguration, punishment, and wedding.